Projections from the lateral vestibular nucleus to the spinal cord in the mouse - Liang, H.; Bácskai, T.; Watson, Charles; Paxinos, G. (Springer, 2013)
The present study investigated the projections from the lateral vestibular nucleus (LVe) to the spinal cord using retrograde and anterograde tracers. Retrogradely labeled neurons were found after fluoro-gold injections into both the cervical and lumbar cord, with a smaller number of labeled neurons seen after lumbar cord injections. Labeled neurons in the LVe were found in clusters at caudal levels of the nucleus, and a small gap separated these clusters from labeled neurons in the spinal vestibular nucleus (SpVe). In the anterograde study, BDA-labeled fiber tracts were found in both the ventral and ventrolateral funiculi on the ipsilateral side. These fibers terminated in laminae 6–9. Some fibers were continuous with boutons in contact with motor neurons in both the medial and lateral motor neuron columns. In the lumbar and sacral segments, some collaterals from the ipsilateral vestibulospinal tracts were found on the contralateral side, and these fibers mainly terminated in laminae 6–8. The present study reveals for the first time the fiber terminations of the lateral vestibular nucleus in the mouse spinal cord and therefore enhances future functional studies of the vestibulospinal system.